Nalar Kesetaraan Mahar dalam Perspektif Syariah Islam - Subhan Subhan (JURNAL AT-TURAS, 2018)
Presenting dowry (mahar) in the process of marriage is an ancient tradition since Jahiliyah period. Since that era, dowry was more meaningful as transactional instrument between husband’s family as buyer and male members of wife’s family as seller. The position of wife is extremely disadventaged, because they are considered as ‘potential’ commodity to get financial income for male members of wife’s family. When Al-Quran has been revealed, the tradition of dowry continued, but its conception has changed. If at the past time dowry was paid for the parents or family members of wife, today dowry is paid for the wife. Furthermore, Al-Quran changed status of woman from merely ‘commodity’ to actively participant in that transaction. The meaning of dowry in this period has changed from only a symbol of transaction to symbol of compassion and love; it is also a symbol of wedlock to provide wife material and moral support. In Islamic tradition, presenting dowry is an obligation. A man who get married with woman is obliged to present her a dowry, and he commits a sin if he does not present her a dowry.